Perubahan Histologik Postmortem pada Kelenjar Brunner Hewan Coba - Sartika, Reza S.; Wongkar, Djon; Kalangi, Sonny J.R. (Universitas Sam Ratulangi, 2018)
Abstract: Studies of postmortem histological changes in digestive system showed a variety of changes related to postmortem time. This study was aimed to obtain the histological changes of Brunner gland within 24-hour interval using a domestic pig as model. This was a descriptive study. Samples of duodenum were taken at several time intervals, as follows: 0 hour, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, and 24 hours. The results showed that the earliest histological changes occurred at 3 hours postmortem which showed congestion, widened gland lumen, as well as hydrophic degeneration of gland cells. At 7 hours to 22 hours postmortem the changes became more visible and were associated with lysis of the gland cells. At 24 hours postmortem the lysis had covered >50% of the gland cells, however, the Brunner glands could still be identified. Conclusion: The earliest changes occured at 3 hours postmortem in the forms of congestion, widened gland lumens, and hydrophic degeneration of gland cells which became more visible at 7-22 hour postmortem associated with gland cell lysis. The cell lysis covered most of the gland cells at 24 hours postmortem, however, the Brunner glands could still be identified.Keywords: duodenum, autolysis, postmortem.Â Abstrak: Berbagai penelitian mengenai perubahan histologik postmortem dari organ sistem pencernaan telah dilakukan pada hewan coba yang memperlihatkan variasi perubahan histologik sehubungan dengan waktu postmortem. Penelitian ini bertujuan untuk mendapatkan gambaran perubahan histologik postmortem pada kelenjar Brunner hewan coba dengan interval waktu 24 jam. Jenis penelitian ialah deskriptif yang menggunakan babi domestik sebagai hewan coba. Interval waktu pengambilan sampel dari bagian duodenum ialah: 0 jam, 1 jam, 2 jam, 3 jam, 4 jam, 5 jam, 6 jam, 7 jam, 8 jam, 9 jam, 10 jam, 12 jam, 14 jam, 16 jam, 18 jam, 20 jam, 22 jam, dan 24 jam postmortem. Hasil penelitian mendapatkan bahwa perubahan awal terjadi pada 3 jam postmortem yang menunjukkan kongesti dan lumen kelenjar melebar, serta degenerasi hidropik pada sel-sel kelenjar Brunner. Perubahan semakin tampak pada 7 jam sampai 22 jam postmortem, dan mulai terjadi lisis sel-sel kelenjar Brunner. Pada 24 jam postmortem lisis yang terjadi telah mencapai sekitar 50% sel kelenjar tetapi kelenjar Brunner masih dapat diidentifikasi. Simpulan: Perubahan awal terjadi pada 3 jam postmortem yang menunjukkan kongesti dan lumen kelenjar melebar serta degenerasi hidropik pada sel-sel kelenjar Brunner yang terus berlangsung disertai lisis sel-sel kelenjar yang pada 24 jam postmortem telah mencapai sebagian besar sel kelenjar tetapi kelenjar Brunner masih dapat diidentifikasi.Kata kunci: duodenum, autolisis, postmortem